2002
DOI: 10.1103/physrevb.65.144447
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and dilution effects of the kagomé bilayer geometrically frustrated network: A Ga NMR study ofSrCr9pGa129p

Abstract: The archetype of geometrically frustrated compounds SrCr 9 p Ga 12Ϫ9 p O 19 is a kagomé bilayer of Heisenberg Cr 3ϩ ions (Sϭ3/2) with antiferromagnetic interactions. We present an extensive gallium nuclear magnetic resonance ͑NMR͒ study over a broad Cr-concentration range (0.72рpр0.95). This allows us to probe locally the susceptibility of the kagomé bilayer and separate the intrinsic properties due to geometric frustration from those related to site dilution. Compared to the partial study on one sample, pϭ0.9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
102
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 70 publications
12
102
0
1
Order By: Relevance
“…The disorder in this compound stems from the dilution of the Cr sublattice by nonmagnetic Ga 3+ ions. The magnetic susceptibility measurements (macroscopic, χ macro , in contrast to local measurements by NMR technique [10]) suggest the occurrence of spin glass state with spin freezing temperature T g ≈ 2-5 K [11][12][13][14][15]. All other experimental data confirms existence of a spin-liquid-like ground state [12,16,17].…”
Section: Kagome Antiferromagnet Srgasupporting
confidence: 55%
See 2 more Smart Citations
“…The disorder in this compound stems from the dilution of the Cr sublattice by nonmagnetic Ga 3+ ions. The magnetic susceptibility measurements (macroscopic, χ macro , in contrast to local measurements by NMR technique [10]) suggest the occurrence of spin glass state with spin freezing temperature T g ≈ 2-5 K [11][12][13][14][15]. All other experimental data confirms existence of a spin-liquid-like ground state [12,16,17].…”
Section: Kagome Antiferromagnet Srgasupporting
confidence: 55%
“…exchange interactions other than nearest-neighbor interaction, magnetic anisotropy of Cr 3+ ions and dipolar anisotropy), usually suppressing spin liquid state, are very small compared to the Cr-Cr interactions in this kagome lattice. The results obtained in [10] show that NMR is a very powerful technique allowing to measure directly intrinsic frustration effects through determination of χ frustr . It was shown that a maximum in χ frustr occurs in SrGa 12−x Cr x O 19 at temperatures of about 0.1θ where θ is the Curie-Weiss temperature determined using χ macro at high-temperature region.…”
Section: Kagome Antiferromagnet Srgamentioning
confidence: 95%
See 1 more Smart Citation
“…1), which is not observed in the Gd compound. This discrepancy could arise either because of a muon induced effect or possibly a small impurity phase detected by bulk susceptibility, but which contributes nothing to local probe measurements [21]. Alternatively, the contact hyperfine and/or dipolar field could be temperature dependent.…”
mentioning
confidence: 99%
“…Since 71 Ga(4f) nuclei are strongly coupled only to chromium ions within the kagomé bilayer one can single out just the intrinsic susceptiblity of the latter, whereas the macroscopic susceptibility detects also the contribution from defects. [6] …”
Section: Line Shift and Line Widthmentioning
confidence: 99%